Unusual presentation of cutaneous leiomyoma - Sapnashree Bhaskar; Ashok K Jaiswal; S M Madhu; K V Santosh (Wolters Kluwer Medknow Publications, 2014)
Herein, we report a case of leiomyoma cutis because of its rarity and unusual presentation. The case presented with a solitary leiomyoma lesion which was painless. However, the adjacent normal appearing area was tender. A biopsy of the lesion as well as of a portion of the adjacent normal appearing area was taken, which confirmed the diagnosis of cutaneous leiomyoma. This may suggest the dormant nature of the disease which has not yet become apparent.